The Acute and Longer-Term Effects of Cold Water Immersion in Highly-Trained Volleyball Athletes During an Intense Training Block - Tavares, Francisco; Simões, Mário; Matos, Bruno; Smith, Tiaki Brett; Driller, Matthew (Frontiers in Sports and Active Living, 2020)
Background: The use of cold water immersion (CWI) as a recovery strategy following exercise has drawn mixed findings over the last few decades. The purpose of the current study was two-fold; 1) to determine the acute effects of CWI within the training week, and 2) to investigate the chronic effects of CWI over a 16-day period. Methods: In a randomized, controlled trial, 13 national-level volleyball athletes were allocated to two groups, an experimental (CWI, n=7) and a control group (n=6) during a 3-week national training camp. The experimental group were exposed to a CWI protocol after the last training session of each day (12 CWI sessions). Measures of lower (countermovement jump and squat jump height) and upper-body (medicine ball throw distance) power were collected pre- and post-training camp. Perceptual and neuromuscular performance measures (countermovement jump) were obtained during the training camp. Results: No significant differences between groups were observed for any measure (p > 0.05), however, small effect sizes were observed between experimental and control groups on day two of weeks one and two. Three weeks of training resulted in a significant decrease in countermovement jump height in the control group. Moderate effect sizes (d=0.65) were found for countermovement jump between the experimental and control groups. Conclusion: Cold water immersion seems to provide little benefit to recovery in the acute setting (within the training week), however, chronically, there was a trend towards a benefit when implementing cold water immersion in well-trained volleyball athletes over 16 days.